Daya Juang Mahasiswa Asing - Wiwit Salindri Kusuma Wardani; Satih Saidiyah (Psympathic : Jurnal Ilmiah Psikologi, 2016)
This research aims to describe  adversity quotient and its supporting factor among foreign students. Subjects are students from Thailand studying at  State Islamic University Sunan Kalijaga Yogyakarta. This research applied qualitative approach using phenomenology in order to  obtain the meaning of adversity quotient. The result shows some themes which are (1) controlling the problems by following many organizations, association, and remembering the struggles of parents, (2) being responsible for completing assignment, (3) being capable to limit the issue so that will not interfere other activities, and (4 ) being able to survive by having  principle that there always be an easiness for every difficulties. Factors influencing the adversity quotient are self-motivation and support from surrounding especially parents, confidence to finish college well, and individual characters. Characters like quiet, shy and not confidence inhibiting adversity quotient while friendly and easy going supporting the adversity quotient.